Sex- and age-specific regulation of ACE2: Insights into severe COVID-19 susceptibility. (March 2022) - Viveiros, Anissa; Gheblawi, Mahmoud; Aujla, Preetinder K.; Sosnowski, Deanna K.; Seubert, John M.; Kassiri, Zamaneh; Oudit, Gavin Y.
Abstract: Aged males disproportionately succumb to increased COVID-19 severity, hospitalization, and mortality compared to females. Angiotensin-converting enzyme 2 (ACE2) and transmembrane protease, serine 2 (TMPRSS2) facilitate SARS-CoV-2 viral entry and may have sexually dimorphic regulation. As viral load dictates disease severity, we investigated the expression, protein levels, and activity of ACE2 and TMPRSS2. Our data reveal that aged males have elevated ACE2 in both mice and humans across organs. We report the first comparative study comprehensively investigating the impact of sex and age in murine and human levels of ACE2 and TMPRSS2, to begin to elucidate the sex bias in COVID-19 severity. Graphical abstract: Unlabelled Image Highlights: Aged males experience increased COVID-19 severity. SARS-CoV-2 viral load is positively associated with morbidity and mortality. Tissue levels of viral entry factors may alter susceptibility to severe disease. ACE2 is differentially expressed across sex and age in mouse and human organs. Increased severity in aged males may result from increased ACE2 compared to females.